Types And Levels Of Education In The National Education System In Indonesia - Via Septiani (ATTAQWA: Jurnal Pendidikan Islam dan Anak Usia Dini, 2023)
Education is a very important thing in human life so that they can compete in the future. Education also varies over time, so in education that has the development of cognitive and intellectual goals for students and also education that always encourages moral and ethical education in students. This research is aimed at describing and analyzing a national education system which is mentioned in law number 20 of 2003, which consists of types, pathways and levels of education. The national education system, which consists of types, pathways and levels of education, must be supported by quality human resources and supporting facilities. Law No. 20 of 2003 in article 15 explains that the types of education are general, vocational, academic, professional, vocational, religious and special education. There are 8 types of education consisting of: general education, (2) vocational education, (3) academic education, (4) professional education, (5) vocational education, (6) religious education, (7) special education, (8) official education.